2001
DOI: 10.1111/j.1525-1497.2001.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Discussions About Advance Directives on Patients' Satisfaction with Primary Care

Abstract: BACKGROUND: Discussions of end-of-life care should be held prior to acute, disabling events. Many barriers to having such discussions during primary care exist. These barriers include time constraints, communication difficulties, and perhaps physicians' anxiety that patients might react negatively to such discussions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 24 publications
4
81
0
1
Order By: Relevance
“…Such discussions may have the added potential benefit of long-term improvement in patient satisfaction. 24 The rates of consent for organ donation in the intervention and control arms compared favorably to that of other studies, 2 but were lower than those seen when the same video was shown to individuals applying for their first driver's license at the bureau of motor vehicles. 1 One potential reason for the difference was the disparate study populations.…”
Section: Discussionmentioning
confidence: 55%
“…Such discussions may have the added potential benefit of long-term improvement in patient satisfaction. 24 The rates of consent for organ donation in the intervention and control arms compared favorably to that of other studies, 2 but were lower than those seen when the same video was shown to individuals applying for their first driver's license at the bureau of motor vehicles. 1 One potential reason for the difference was the disparate study populations.…”
Section: Discussionmentioning
confidence: 55%
“…49e51 Previous studies have shown that patients are more satisfied with their GP when advance directives are discussed. 49 Moreover, it could be a satisfactory experience for the physician as well. 52 Altogether, the extent to which ACP truly occurs in advance of future medical decision making is questionable.…”
Section: Discussionmentioning
confidence: 99%
“…A critical tool to achieving this is adequate documentation of patient preferences within the medical record, which helps to ensure that patient wishes are communicated and acted on across care settings and providers, and has been shown to increase patient autonomy in decision making and to decrease resource use. 1 Unfortunately, evidence suggests that documentation of preferences among patients with cancer is suboptimal, [2][3][4] and as a result, providers are often unaware of their patients' preferences regarding treatment. [5][6][7][8] In addition to adequate documentation of preferences, a growing body of literature has highlighted the relevance of having early and regular discussions about patient preferences to improving the quality of cancer care.…”
Section: Introductionmentioning
confidence: 99%